Do we need new high-risk criteria for surgically treated renal cancer patients to improve the outcome of future clinical trials in the adjuvant setting?: Results of a comprehensive analysis based on the multicenter CORONA database - Wolff, Ingmar; May, M.; Hoschke, B.; Zigeuner, R.; Cindolo, L.; Hutterer, G.; Schips, L.; De Cobelli, O.; Rocco, B.; De Nunzio, C.; Tubaro, A.; Coman, I.; et al. (European journal of surgical oncology, 2016)
Background - Since there is still an unmet need for potent adjuvant strategies for renal cancer patients with high progression risk after surgery, several targeted therapies are currently evaluated in this setting. We analyzed whether inclusion criteria of contemporary trials (ARISER, ASSURE, SORCE, EVEREST, PROTECT, S-TRAC, ATLAS) correctly identify high-risk patients. - Methods - The study group comprised 8873 patients of the international CORONA-database after surgery for non-metastatic renal cancer without any adjuvant treatment. Patients were divided into potentially eligible high-risk and assumable low-risk patients who didn't meet inclusion criteria of contemporary adjuvant clinical trials. The ability of various inclusion criteria for disease-free survival (DFS) prediction was evaluated by Harrell's c-index. - Results - During a median follow-up of 53 months 15.2% of patients experienced recurrence (5-year-DFS 84%). By application of trial inclusion criteria, 24% (S-TRAC) to 47% (SORCE) of patients would have been eligible for enrollment. Actual recurrence rates of eligible patients ranged between 29% (SORCE) and 37% (S-TRAC) opposed to <10% in excluded patients. Highest Hazard Ratio for selection criteria was proven for the SORCE-trial (HR 6.42; p < 0.001), while ASSURE and EVEREST reached the highest c-index for DFS prediction (both 0.73). In a separate multivariate Cox-model, two risk-groups were identified with a maximum difference in 5-year-DFS (94% vs. 61%). - Conclusion - Results of contemporary adjuvant clinical trials will not be comparable as inclusion criteria differ significantly. Risk assessment according to our model might improve patient selection in clinical trials by defining a high-risk group (28% of all patients) with a 5-year-recurrence rate of almost 40%.
Gesehen am 18.02.2021